A new code design for spectral amplitude coding optical CDMA systems using fiber bragg-grating - Thanaa Hussein, Abd.; Syed Alwee Aljunid, Syed Junid, Assoc. Prof. Dr.; Hilal Adnan, Fadhil, Dr. (Spinger, 2013)
Link to publisher's homepage at http://link.springer.com/